Teacher Agency and Pedagogical Innovation in Islamic Elementary Education: A Conceptual Review of Curriculum Demands and Classroom Realities - Munir Yusuf (Institut Agama Islam Negeri Palopo, 2025)
Contemporary curriculum reforms, the increasing demand for pedagogical innovation, and the complexity of classroom realities have positioned teachers as central actors in Islamic elementary education. Yet pedagogical innovation is often discussed primarily in terms of new methods, digital tools, or instructional models, while the teacher’s professional capacity to interpret, negotiate, and enact curriculum expectations remains insufficiently theorized. This article aims to conceptualize teacher agency as a mediating capacity that connects curriculum demands with pedagogical innovation in Islamic elementary education. Employing library research with a conceptual review design, the study synthesizes recent scholarly literature on teacher agency, curriculum reform, pedagogical innovation, classroom realities, and Islamic education. The review indicates that teacher agency is not merely a matter of individual autonomy or creativity, but a reflective, ethical, and context-responsive professional capacity through which teachers translate curriculum expectations into meaningful, adaptive, value-oriented, and developmentally appropriate learning practices. The article concludes that strengthening teacher agency is essential for sustaining pedagogical innovation in Islamic elementary classrooms. Future empirical studies are recommended to examine how this conceptual framework operates in madrasah ibtidaiyah and Islamic elementary school contexts.